Background parenchymal uptake on molecular breast imaging as a breast cancer risk factor: a case-control study. Issue 1 (December 2016) - Hruska, Carrie; Scott, Christopher; Conners, Amy; Whaley, Dana; Rhodes, Deborah; Carter, Rickey; O'Connor, Michael; Hunt, Katie; Brandt, Kathleen; Vachon, Celine
Abstract Background Molecular breast imaging (MBI) is a functional test used for supplemental screening of women with mammographically dense breasts. Additionally, MBI depicts variable levels of background parenchymal uptake (BPU) within nonmalignant, dense fibroglandular tissue. We investigated whether BPU is a risk factor for breast cancer. Methods We conducted a retrospective case-control study of 3027 eligible women who had undergone MBI between February 2004 and February 2014. Sixty-two incident breast cancer cases were identified. A total of 179 controls were matched on age, menopausal status, and MBI year. Two radiologists blinded to case status independently assessed BPU as one of four categories: photopenic, minimal to mild, moderate, or marked. Conditional logistic regression analysis was performed to estimate the associations (OR) of BPU categories (moderate or marked vs. minimal to mild or photopenic) and breast cancer risk, adjusted for other risk factors. Results The median age was 60.2 years (range 38–86 years) for cases vs. 60.2 years (range 38–88 years) for controls (p = 0.88). Women with moderate or marked BPU had a 3.4-fold (95 % CI 1.6–7.3) and 4.8-fold (95 % CI 2.1–10.8) increased risk of breast cancer, respectively, compared with women with photopenic or minimal to mild BPU, for two radiologists. The results were similar after adjustment for BI-RADS density (OR 3.3 [95 % CI 1.6–7.2] and OR 4.6 [95 % CI 2.1–10.5]) or postmenopausal hormone use (OR 3.6 [95 % CI 1.7–7.7] and OR 5.0 [95 % CI 2.2–11.4]). The association of BPU with breast cancer remained in analyses limited to postmenopausal women only (OR 3.8 [95 % CI 1.5–9.3] and OR 4.1 [95 % CI 1.6–10.2]) and invasive breast cancer cases only (OR 3.6 [95 % CI 1.5–8.8] and OR 4.4 [95 % CI 1.7–11.1]). Variable BPU was observed among women with similar mammographic density; the distribution of BPU categories differed across density categories (p < 0.0001). Conclusions This study provides the first evidence for BPU as a risk factor for breast cancer. Among women with dense breasts, who comprise >40 % of the screening population, BPU may serve as a functional imaging biomarker to identify the subset at greatest risk.